Therapeutic Outcomes Associated with Augmented Renal Clearance in Trauma Patients of the ICU at UGM Academic Hospital - Annafi' Nanda Rohmah Utami; Ika Puspitasari; Tri Murti Andayani (Academic Hospital Journal, 2026)
Background: Augmented Renal Clearance (ARC) occurs in intensive care units (ICUs) and results in increased drug clearance in critically ill patients. Trauma patients have a twofold higher risk of ARC. ARC can increase the risk of subtherapeutic drug dosing and therapeutic failure. This study aims to determine the characteristics of trauma patients with and without ARC and to investigate the association between ARC and therapeutic outcomes, including length of stay and clinical outcomes, in trauma patients admitted to the ICU at UGM Academic Hospital.Method: This study is an analytical observational study with a retrospective cohort design. The population in this study consists of adult patients diagnosed with trauma in the ICU at UGM Academic Hospital during the period from January 2021 - April 2024 who met the inclusion and exclusion criteria. Descriptive analysis was used to examine the characteristics of trauma patients in the ICU, with results presented in tables as percentages and mean values. An independent t-test was used to determine the difference in length of stay (LOS) between patients with and without ARC. The Chi-Square test was conducted to assess the association between ARC and clinical outcomes.Result:  The study population comprised 35 trauma patients in the ARC group and 49 in the non-ARC group. Both groups were predominantly male, with the mean age of trauma patients with ARC being younger (34.49 ± 13.38 years). ARC was characterised by lower serum creatinine levels and higher creatinine clearance. Trauma patients with ARC had a higher mean APACHE II score (9.69 ± 6.88) but a lower mean CCI score (0.54 ± 0.74). Trauma patients with ARC showed lower mean initial and final GCS scores (11.23 ± 4.12 and 11.63 ± 5.12, respectively). The mean leukocyte count in the ARC group was higher (16.57 ± 6.45 × 10³/µL), and the group had a higher infection rate (51.4%, n = 18). The mean LOS for trauma patients with ARC was longer (11.77 ± 15.35 days), but did not differ significantly from that of patients without ARC (p = 0.055). The number of trauma patients with ARC who did not show clinical improvement was significantly higher (28.6%, n = 10; p = 0.005).Conclusion: The mean LOS of trauma patients with ARC is longer, showing a tendency towards significance. ARC is associated with worse clinical outcomes in trauma patients in the ICU, as demonstrated by poor clinical outcomes in 10 patients.